Business intelligence and data analytics framework: case study of humanitarian organisations refugees' registration system. (7th March 2022) - Ballout, Amal; Alhasan, Mays; Fraihat, Salam; Elhassan, Ammar
Business intelligence and analytics has gained prominent focus among organisations with information systems that collect and process vast amounts of data. Voluminous, unprocessed data does not lend itself to offering useful insights for businesses, especially with basic statistical methods and traditional reporting techniques. In this work, we design a business intelligence and data analytics framework for refugee registration system serving over six million refugees to collect, collate and filter demographic data. The proposed reporting mechanism leverages the power of interactive dashboards to offer informative and intuitive reports and visualisations that are accessible and interpretable by stakeholders.